Company performance in Nigerian listed companies: Do large shareholders expropriate minority shareholders? - Odewale, Robert W.; Kamardin, Hasnah (MCSER Publishing, Rome-Italy, 2015)
It is argued that large shareholders have enormous influence over their companies as their ability to monitor the executives can mitigate the agency problems.This paper examines how large shareholders are related to company performance after distinguishing domestic large shareholders from the foreign large shareholders Using a panel of 58 companies listed on the Nigerian Stock Exchange with 222 company-year observations from 2009 to 2012, firm-level fixed effects regression was used for analysis.We find evidence that domestic large shareholders are associated with better company performance while foreign large shareholders show a concave relationship with company performance with inflection point at 31.88%.The empirical result also shows that the joint presence of the both domestic large shareholders and foreign large shareholders in companies seems to make them pursue overall wealth maximization objective of the company.The result is consistent with the contention that concentrated ownership remains an effective corporate governance mechanism in an environment with weak investor protection rights.The study contributes to the corporate governance literature of the substitution effect of large shareholders for effective corporate governance practice.